1975
DOI: 10.1073/pnas.72.7.2714
|View full text |Cite
|
Sign up to set email alerts
|

New histones found in mature mammalian testes.

Abstract: Two new histones have been found in sexually mature testes of several mammals. The new histones have been identified as a new F1 (TFI) and F2b (TF2b) on the basis -of their behavior upon chemical fractionation procedures and electrophoresis at several urea concentrations. The new testis-specific histones are absent in very immature animals and in somatic tissues. However, by day 20, in the rat, the histone pattern is that of the adult, displaying nearly a full complement of TF1 and TF2b. The new histone comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 19 publications
5
40
0
Order By: Relevance
“…Two of them, THi (3,19), but the two histones have significant differences in their lysine and valine contents. TH2B is a variant of H2B (4), as demonstrated by amino acid analysis, molecular weight determinations, and chemical fractionation. The main difference between them is that TH2B contains cysteine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them, THi (3,19), but the two histones have significant differences in their lysine and valine contents. TH2B is a variant of H2B (4), as demonstrated by amino acid analysis, molecular weight determinations, and chemical fractionation. The main difference between them is that TH2B contains cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we describe the appearance, synthesis, and turnover of two testis-specific histones, testis H1(TH1) and testis H2B (TH2B); these histones are closely related, by molecular weight and amino acid composition, to the somatic histones H1 and H2B, respectively (3,4).…”
mentioning
confidence: 99%
“…The mammalian histone H2B variant TSH2B was initially found in histone extracts from rat testes (Branson et al, 1975;Shires et al, 1975). Genomic and genetic analyses revealed that the mouse TSH2B homologue, TH2B, functions in genome-wide histone-protamine exchange during spermatogenesis (Govin et al, 2007;Montellier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant with these visible changes in chromatin organization, the histone and nonhistone proteins are removed from the DNA and replaced for a period of time by several transition proteins . These proteins are subsequently replaced by protamine during the final stages of spermatid maturation, chromatin reorganization and condensation (11,12,14,35,36,48,56,61,71,76,78,85) .…”
mentioning
confidence: 99%